The Government of Self and Others - Davidson, Arnold I. author. aut Link
XVII, 402 p.
Keywords: An exciting and highly original examination of the practices of truth-telling and speaking out freely (parr?sia) in ancient Greek tragedy and philosophy. Foucault discusses the difficult and changing practices of truth-telling in ancient democracies and tyrannies and offers a new perspective on the specific relationship of philosophy to politics.